(untitled) (Journal of Humanities and Social Sciences Research, 2023)
Rhythmic gymnastics is a core subject in the curriculum of the Faculty of Physical Education and Sports Sciences for Girls, which makes it difficult for beginners to deal with tools and performance difficulties. Students may be exposed to a state of hesitation that negatively affects the performance of the kinetic composition and requires self-esteem so that they can perform properly. I touched on the community and the sample of the research, where the sample of the research was randomly selected so that the sample of the research, 107 of its students, was distributed to the quadrant division (a). b. c. d). The findings were presented and analysed, and for the most important conclusions and recommendations, where the most important conclusions were: through presentation, analysis and discussion of the findings, the researcher reached the following conclusions: • A moral correlation between self-esteem level and motor formation performance in rhythmic gymnastics. • There are moral differences in the level of self-esteem among female students. • There are moral differences in the performance level of the kinetic formation in the rhythmic gymnastics of students. • Self-esteem plays a positive role in the performance of the motor formation in rhythmic gymnastics. Recommendations: Through the study’s findings, the researcher developed the following recommendations: - Interest in strengthening students’ self-esteem through a targeted curriculum. - Periodic tests of the measure of self-esteem and of all stages. - Conducting research and studies on subjects dealing with other variables relating to psychological measures and performance of students’ mobility; - Attention to the psychological aspect of the student’s physical and skill aspects.